(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Feminist science and technology studies have influenced our developing knowledge of sex, gender, and biotechnology for three decades. We tend to think of sex and gender in binary terms, which significantly limits our understanding of human variety as well as advances in science and technology. The Indian Genome Variation Project and transnational surrogacy are used as case studies in this article to examine how popular biotechnology views are reduced to binary stances that promote and oppose biotechnology as a solution for India’s economic and social progress. The article contends that the effect of surrogacy and genomics on women and gender is much more complicated since they are situated within the broader geopolitical, historical, economic and cultural changes of postcolonial India. What is it about technology that makes it a significant source of future hope? Is it because of genomics’ promise of excellent health that it has become the location for such promises? Why has India become a popular destination for transnational surrogacy and other forms of reproductive tourism? For this reason, the article makes a case for the social studies of science to show that technology and human beings are never really neutral. These colonial and postcolonial histories of science and technology should inform our understanding of surrogacy and genomics.